ACUTE POISONINGS IN A CHILDREN'S EMERGENCY DEPARTMENT. Issue 1 (14th December 2015) - Starkey, Elizabeth; Sammons, Helen
Abstract : Objective: To determine the incidence of children presenting to a children's emergency department with acute ingestion or poisoning. To identify common substances involved and those requiring admission and/or treatment. Method: A retrospective notes survey was performed in children <16 years with a diagnosis of overdose or poisoning attending the local emergency department in 2013. Results: A total of 441 events occurred with a potential diagnosis of overdose or poisoning in 428 children. This was 1.46% of all emergency attendances. 223 events (50%) were under 5 years with medicines or soaps and detergents being the commonest causes of accidental ingestion in 40% and 21% respectively. 182 events were over 12 years; 137 due to self-harm, 25 from alcohol and 9 from illicit drugs. 40% of all events required admission; 77% and 97% staying less than 24 and 48 hours respectively. In those staying over 2 days, only 1 patient remained for medical reasons requiring PICU care for a significant alcohol overdose. 10 patients received HDU care, 9 for close observation and 1 for treatment of recurrent seizures post mixed overdose. Only 2 patients had severe symptoms defined by the poisoning severity score. Conclusion: Acute poisoning is a common reason to attend paediatric emergency departments. Most under 5 years don't require admission or treatment whereas over 12 years poisonings and overdoses are more problematic. Severe symptoms in children are rare suggesting further studies are required for determining the incidence of severe paediatric poisonings within the UK and Europe.